Study on effect of TiB2 reinforcement on the microstructural and mechanical properties of magnesium RZ5 alloy based metal matrix composites - Arabinda Meher; Manas Mohan Mahapatra; Priyaranjan Samal; Pandu R. Vundavilli (Journal of Magnesium and Alloys, 2020)
A self-propagating high-temperature synthesis route is adopted for the fabrication of TiB2-reinforced magnesium RZ5 alloy-based in-situ metal matrix composites. Ti-B is used according to the appropriate stoichiometry to obtain 4, 6 and 8 wt.% TiB2 reinforcements. The base alloy and cast composites are solutionised to enhance the mechanical properties of the materials. A microstructural study of the composites is carried out using optical microscopy and field emission scanning electron microscopy (FESEM) and revealed near-uniform distribution of TiB2 particles in the magnesium RZ5 alloy matrix. X-ray diffraction revealed the formation of the TiB2 reinforcement along with the transient phase TiB and MgB7. The hardness of the RZ5 alloy-based composites increases by 7.12%, 17.06% and 32.07% with the addition of 4, 6 and 8 wt.% TiB2 reinforcements, respectively. The ultimate tensile strength of the as-cast composite increases by 30.47% with the addition of 8 wt.% TiB2. The tensile strength and ductility of the materials is improved by using the solutionising heat treatment. The heat-treated composite containing 8 wt.% TiB2 results in an ultimate tensile strength of 178.7 MPa. The tensile fracture surfaces are analysed using FESEM. The wear loss of the materials decreased from 25.826 mm3 to 22.949 mm3 by the adding 8 wt.% TiB2 for the sliding distance of 2000 m. Micrographs of the worn surfaces obtained from FESEM of both the base alloy and composites are also studied which indicate delamination, wear groove and oxide formation.